ANALISIS PRODUKTIVITAS MESIN FILLING KRIM PADA PT. XYZ DENGAN MENGGUNAKAN METODE OVERALL EQUIPMENT EFFECTIVENESS - Isya Nafia; Azizah Nur Kamila; Andhika Putrana Isdy; Muchammad Fauzi (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2022)
This study aims to determine the value of the OEE (Overall Equipment Effectiveness) factor on the cream filling machine at PT XYZ. OEE is one of the standards for measuring manufacturing productivity and identifying the percentage of production time that is productive. OEE Is the single best metric for identifying losses, comparing progress, and increasing productivity of manufacturing equipment. This research was conducted at the company PT. XYZ by taking production data for the period November 2020 - February 2021 on the cream filling machine at the company PT XYZ. Based on data processing carried out on the cream filling machine at PT XYZ, in OEE 3 measurement factors are used as references to determine the OEE value on a machine, including Availability, Performance, Quality, the results of the availability, performance, and quality measurements are 90, 64%, 97.27%, and 97.52%, it can be seen that the Rate of Quality in this filling machine is 97.52%, which means that the product does not meet the World Class requirements, namely > 99.9%. The results of OEE obtained are 85.97%. It can be concluded that the OEE value of the cream filling machine at PT XYZ meets the World Class OEE requirements, namely > 85%